Pengaruh lama pemberian aspirin pada ekspresi protein KI-67 dan ketebalan epitel mukosa rongga mulut tikus Wistar jantan (The effect of aspirin administration period on KI-67 expression protein and oral epithelial mucosal thickness in male Wistar mice) - Dian Yosi Arinawati; Heni Susilowati; Supriatno Supriatno (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2014)
Background: Aspirin has been widely used as an anti-inflammatory, antipyretic, and analgesics drugs. It has seriously side effects like gastrointestinal ulceration, delayed healing ulcer, and oral mucosal ulceration when Aspirin is administered for long time. Purpose: The aim of study was to examine the effect of Aspirin administration period on Kiehl-67 (KI-67) protein expressions and oral mucosal epithelial thickness in male Wistar mice. Methods: Experimental laboratory study with post-test only control group design was performed and 40 male Wistar mice were used in this experiment. The samples were divided into 2 groups. Group I was treated with Aspirin, whereas group II was receive aquadest. Each group was divided into 5 subgroups for assessment of the length administration effect. All of mice were sacrificed on day 1, 3, 5, 7 and 10 after treatment. Aspirin was orally administrated with doses of 9 mg/kg body weight. The buccal right of mice oral mucosal tissue was sliced and delivered for immunohistochemistry staining using anti-KI-67. Hematoxylin-eosin (HE) staining was performed to measure the oral epithelial thickness. Examination of KI-67 expressions and oral epithelial thickness were performed by using ImageJ software. Two-way Anova and Kruskall-Wallis test were carried-out for data analysis with significant level of 95%. Results: The results revealed that the administration of Aspirin in mice on day 1, 3, 5, 7, and 10 was markedly decreased in the KI-67 protein expressions and oral epithelial thickness compared with that of control (p<0.05), otherwise the duration of Aspirin administration did not affect mucosal epithelial thickness. Conclusion: Aspirin administration period has the potential to suppress the KI-67 protein expression within 10 days; the effect in line with the length of duration. The epithelial thickness was not influenced by the length of Aspirin administration.Latar belakang: Aspirin digunakan sebagai anti inflamasi, anti demam, dan anti nyeri. Aspirin merupakan obat yang aman, namun dilaporkan menimbulkan efek samping berupa kerusakan gastrointestinal dan kerusakan mukosa rongga mulut apabila dikonsumsi dalam jangka panjang. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh lama pemberian Aspirin terhadap ekspresi KI-67 dan ketebalan epitel rongga mulut tikus galur Wistar. Metode: Jenis penelitian eksperimental laboratories dan menggunakan 40 tikus jantan galur Wistar. Hewan coba dibagi menjadi 2 kelompok, yaitu kelompok perlakuan Aspirin dan kontrol akuades. Masing-masing kelompok dibagi menjadi 5 subkelompok berdasarkan lama pemberian Aspirin, yaitu 1, 3, 5, 7 dan 10 hari. Dosis yang diberikan 9 mg/kg berat badan sekali per hari. Mukosa bukal tikus kemudian dipotong untuk pengecatan KI-67 dan hematoxylin-eosin (HE). Ekspresi KI-67 dan ketebalan epitel diukur menggunakan software ImageJ. Data dianalisis menggunakan Two-way Anova and KruskallWallis dengan tingkat kepercayaan 95%. Hasil: Lama pemberian Aspirin hari ke 1, 3, 5, 7 dan 10 dapat menurunkan ekspresi KI-67 (p<0.05) dan ketebalan epitel dibandingkan kontrol, namun lama pemberian tidak berpengaruh terhadap mukosa epitel. Aspirin dapat menurunkan ketebalan epitel rongga mulut dibandingkan kontrol (p<0.05). Simpulan: Pemberian Aspirin dapat menurunkan ekspresi KI-67 pada sel epitel mukosa rongga mulut tikus galur Wistar; efek tersebut berbanding lurus dengan durasi pemberian sampai hari ke-10. Lama pemberian Aspirin tidak berpengaruh terhadap ketebalan mukosa rongga mulut tikus galur Wistar.